Impacts of Renewable Energy Transitions on the Economic Growth in Malaysia: A Dynamic ARDL Simulations - Seriram, Nurulhuda; Zainuddin, Muhamad Rias K. V.; Hamidi, Hakimah Nur Ahmad; Abdullah, Amirul Hamza (International Journal of Energy Economics and Policy, 2024)
This study explores the dynamic relationships between renewable energy transitions and economic growth in Malaysia, with a specific focus on hydroelectric power, using the Dynamic Autoregressive Distributed Lag (D-ARDL) simulations. The research leverages extensive time-series data from 1988 to 2022 to analyze the impacts of hydroelectric and non-renewable energy consumption on the nation's economic trajectory. Our findings indicate a positive long-term relationship between hydroelectric power usage and GDP growth, highlighting renewable energy's pivotal role in sustainable economic development. Additionally, the study examines the short-term adjustments and the effectiveness of hydroelectric power in reducing dependence on non-renewable energy sources, which are crucial for achieving Malaysia's Nationally Determined Contributions (NDC) for 2030. The dynamic ARDL simulations provide nuanced insights into the potential future impacts of increased hydroelectric power usage, underscoring its dual benefits for economic growth and environmental sustainability. This research contributes to the understanding of energy transitions within the context of Malaysia's unique economic and environmental landscape, offering implications for policy and investment in renewable energy infrastructure.